Auxetic behavior of 3D woven warp, weft, and bidirectional interlock structures. Issue 1 (31st December 2023) - Ullah, Tehseen; Hussain, Muzzamal; Ali, Mumtaz; Umair, Muhammad
ABSTRACT: Natural fibers are gaining importance due to environmental concerns and sustainability issues. However, their mechanical performance is not up to the mark. To overcome this problem, natural fiber-based 3D woven structures are used in structural applications. The mechanical performance of 3D woven structures can be further enhanced by adding auxetic mechanisms to the structures. Auxetic structures have exceptional mechanical properties due to a negative Poisson's ratio. In the present study, 3D woven orthogonal warp, weft, and bidirectional interlock structures were developed with jute yarn, and the effect of interlocking pattern on the auxeticity and different mechanical properties (tensile, stiffness, tear) of the structures was investigated. The results revealed that the 3D warp interlock structure showed the highest auxeticity, while the bidirectional interlock depicted the least auxeticity. Due to higher auxeticity, the thickness of the warp interlock structure was increased after applying force to it. The change in the thickness of the woven structure also increases its energy dissipation capability. Furthermore, structures having higher auxeticity also manifest higher tensile, stiffness, and tear properties as compared to other structures. The results are also statistically analyzed using one-way ANOVA (Tukey).